Health status improvement with ferric carboxymaltose in heart failure with reduced ejection fraction and iron deficiency. (29th March 2022) - Butler, Javed; Khan, Muhammad Shahzeb; Friede, Tim; Jankowska, Ewa A.; Fabien, Vincent; Goehring, Udo‐Michael; Dorigotti, Fabio; Metra, Marco; Piña, Ileana L.; Coats, Andrew J.S.; Rosano, Giuseppe; Comin‐Colet, Josep; et al.
Abstract : Aim: Intravenous ferric carboxymaltose (FCM) has been shown to improve overall quality of life in iron‐deficient heart failure with reduced ejection fraction (HFrEF) patients at a trial population level. This FAIR‐HF and CONFIRM‐HF pooled analysis explored the likelihood of individual improvement or deterioration in Kansas City Cardiomyopathy Questionnaire (KCCQ) domains with FCM versus placebo and evaluated the stability of this response over time. Methods and results: Changes versus baseline in KCCQ overall summary score (OSS), clinical summary score (CSS) and total symptom score (TSS) were assessed at weeks 12 and 24 in FCM and placebo groups. Mean between‐group differences were estimated and individual responder analyses and analyses of response stability were performed. Overall, 760 (FCM, n  = 454) patients were studied. At week 12, the mean improvement in KCCQ OSS was 10.6 points with FCM versus 4.8 points with placebo (least‐square mean difference [95% confidence interval, CI] 4.36 [2.14; 6.59] points). A higher proportion of patients on FCM versus placebo experienced a KCCQ OSS improvement of ≥5 (58.3% vs. 43.5%; odds ratio [95% CI] 1.81 [1.30; 2.51]), ≥10 (42.4% vs. 29.3%; 1.73 [1.23; 2.43]) or ≥15 (32.1% vs. 22.6%; 1.46 [1.02; 2.11]) points. Differences were similar at week 24 and for CSS and TSS domains. Of FCM patients with a ≥5‐, ≥10‐ or ≥15‐point improvement in KCCQ OSS at week 12, >75% sustained this improvement at week 24. Conclusion: Treatment of iron‐deficient HFrEF patients with intravenous FCM conveyed clinically relevant improvements in health status at an individual‐patient level; benefits were sustained over time in most patients. Abstract : This analysis shows that treating iron‐deficient heart failure with reduced ejection fraction patients with ferric carboxymaltose, an intravenous iron preparation, resulted in a clinically meaningful improvement in health status for individual patients, many of whom experienced a sustained improvement over time.